Elasto-plastic finite element stress analysis of thermoplastic-matrix symmetric cross-ply plates with square hole - Arslan, Nurettin; Turgut, Aydin; Sancaktar, Erol (American Society of Mechanical Engineers (ASME), 2000)
In this study, elasto-plastic stress analysis of symmetric cross-ply reinforced thermoplastic (PVC) matrix composite laminated plates with square hole is presented. A two-dimensional computer program is developed for elasto-plastic stress analysis of laminated plates by FEM. The thermoplastic matrix is reinforced using long stainless steel fibers. The composite plates are manufactured by using molds under the action of 2 MPa pressure, and heating up to 200 °C. The laminated plate with square hole consists of four reinforced layers bonded symmetrically in (JW-Gk) cross-ply configuration. A first-order shear deformation theory, and nine node Lagrangian finite element method are used in analysis. The applied in-plane load, and the layer orientation angle are varied to obtain the corresponding variation of residual stresses, and the expansions of plastic regions for various cases. Copyright © 2000 by ASME
ASME 2000 International Mechanical Engineering Congress and Exposition, IMECE 2000 -- 5 November 2000 through 10 November 2000 -- Orlando -- 173931
Keywords: Elastoplasticity; Laminated composites; Laminating; Plates (structural components); Polymer matrix composites; Polyvinyl chlorides; Reinforced plastics; Reinforcement; Shear deformation; Steel fibers; Stress analysis; Cross-ply; Cross-ply plates; Elasto-plastic stress; Elastoplastics; Finite element stress analysis; Laminated plate; Square holes; Stresses analysis; Symmetrics; Thermoplastic matrix; Finite element method